When the Dance Touches us: meanings, ethics, and presence in practices with touch in the curriculum - Fonseca Falkembach (Universidade Federal de Pelotas – UFPel, Pelotas/RS, Brazil), Maria (Revista Brasileira de Estudos da Presença, 2022)
This article presents an excerpt of the research concerning six dance teachers in southern Brazilian schools, describing dance classes within the Art curriculum through ethnographic approach. The text analyzes dance practices, activities in which the touch is a central component. Starting from Michel Foucault's theoretical perspective, this study identifies tensions concerning the technologies of production of subject-bodies at the school, challenging hegemonic codes of skin and touching. The research singles out the effects of dance practices with touch, mainly regarding: a) the suspension of embodied cultural meanings; b) the dimension of presence; and c) the ethical work.